2022
DOI: 10.1177/10499091221105882
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia Symptoms Among Hospice Family Caregivers: Prevalence and Association with Caregiver Mental and Physical Health, Quality of Life, and Caregiver Burden

Abstract: Background Poor sleep exacerbates mental health problems and reduces quality-of-life (QOL) but prevalence of insomnia symptoms among hospice family caregivers and associations of poor sleep with caregiver health and QOL outcomes are not known. Objective To describe prevalence of insomnia symptoms among hospice family caregivers and compare anxiety, depression, self-rated health, QOL, and caregiver burden between hospice family caregivers with and without insomnia symptoms. Methods Descriptive sub-study using d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
(105 reference statements)
0
6
1
Order By: Relevance
“…Another recent study found that compared to family caregivers of terminally-ill persons without insomnia symptoms, caregivers with insomnia symptoms reported 2.4 times greater mean anxiety scores, 3.5 times greater mean depression scores, 2.1 times greater caregiver burden scores, 1.3 times lower self-rated health scores, and 1.3 times lower total quality-of-life scores (including significantly lower scores in emotional, social, and physical quality-of-life). 26 Furthermore, poor sleep and anxiety symptoms have been found to be associated with poorer health in hospice family caregivers. 18 Research is needed to understand how end-of-life caregiving may be a morbid risk factor for caregiver health and what can be done to mitigate physical and mental health risks.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Another recent study found that compared to family caregivers of terminally-ill persons without insomnia symptoms, caregivers with insomnia symptoms reported 2.4 times greater mean anxiety scores, 3.5 times greater mean depression scores, 2.1 times greater caregiver burden scores, 1.3 times lower self-rated health scores, and 1.3 times lower total quality-of-life scores (including significantly lower scores in emotional, social, and physical quality-of-life). 26 Furthermore, poor sleep and anxiety symptoms have been found to be associated with poorer health in hospice family caregivers. 18 Research is needed to understand how end-of-life caregiving may be a morbid risk factor for caregiver health and what can be done to mitigate physical and mental health risks.…”
Section: Discussionmentioning
confidence: 99%
“…In some ways, hospice family caregivers and new parents are similar: caregiving needs of babies and dying persons are significant and the stresses of caregiving combined with poor sleep have been found to affect the mental health of new mothers 53,54 and hospice family caregivers. 17,26,32 In postpartum women, poor sleep has been found to be independently associated with increased depression and anxiety symptoms. 55,56 For this reason, there is a growing movement to treat and prevent mental health disorders in postpartum women by targeting insomnia with cognitive behavioral therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations